2001
DOI: 10.1116/1.1409390
|View full text |Cite
|
Sign up to set email alerts
|

Reduced brightness of the ZrO/W Schottky electron emitter

Abstract: Experimental evaluation of the extended Schottky model for ZrO/W electron emissionThe reduced brightness for a ͗100͘ ZrO/W Schottky electron emitter with a tip radius of 0.8 m has been measured. The maximum reduced brightness measured was 2ϫ10 8 A/͑m 2 sr V͒. The measurements of the reduced brightness are compared with the extended Schottky theory and the theory on stochastic Coulomb interactions. At high angular current densities the reduced brightness is limited by statistical Coulomb interactions in the gun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 18 publications
2
33
0
Order By: Relevance
“…However, it is known that in situations where a Schottky emitter is operated at higher brightness, Coulomb interactions can limit the effective brightness. 9 In addition, the energy spread may increase because of Boersch effects. 11 Optimizing a system with a Schottky source, taking all Coulomb effects into account with a correctly varying acceleration voltage in the gun segment, requires a separate study.…”
Section: ͑24͒mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that in situations where a Schottky emitter is operated at higher brightness, Coulomb interactions can limit the effective brightness. 9 In addition, the energy spread may increase because of Boersch effects. 11 Optimizing a system with a Schottky source, taking all Coulomb effects into account with a correctly varying acceleration voltage in the gun segment, requires a separate study.…”
Section: ͑24͒mentioning
confidence: 99%
“…The values for the Schottky emitter are conservative: brightness values of 2 ϫ 10 8 have also been demonstrated. 9 Adding a monochromator to a Schottky source has been demonstrated and shown to be of value for high-resolution probes, so we add this case to the comparison, setting the energy width equal to what is obtained intrinsically from a CNT emitter. Note that we use FW50 values for the energy spread; FWHM A / sr at 200 nA emission at 250 V. The extractor for these measurements was at a distance of about 1 mm, so we assume that aberration coefficients of the gun lens will be of that same order.…”
Section: Brightness Definition and Current In A Probementioning
confidence: 99%
“…Unfortunately, it is so that the higher this "intrinsic" practical brightness, the more important the effect of Coulomb interactions becomes. For Schottky emitters, it has been shown that interactions become important when the intrinsic practical brightness exceeds ϳ3 ϫ 10 8 A / m 2 sr V. 12 For the new source types based on carbon nanotubes 13 and nanotips, 14 we expect their practical brightness to be largely determined by the Coulomb interactions.…”
Section: Coulomb Interactions Close To the Emittermentioning
confidence: 99%
“…According to Van Veen et al [Vee01] the Holtsmark regime is the relevant regime for the trajectory displacement in beams from the end facet of a Schottky emitter.…”
Section: Calculation Of the Trajectory Displacementmentioning
confidence: 99%
“…A correct method would be a convolution, but it is more practical to have some power addition rule to add two numbers that characterize the distributions. What is often used, is the quadratic addition of the FWHM of the distributions [Fra98,Vee01,Sak03], but this is a valid method only for two Gaussian distributions. According to Jansen [Jan90] the FW50 of two intensity distributions of different shape can be added using γ 1 and γ 2 correspond to the shape of the distributions to be added: e.g.…”
Section: Adding Contributions Togethermentioning
confidence: 99%